Power spectra of convective motions in the solar photosphere - Baran, O.A. (Advances in Astronomy and Space Physics, 2013)
We reproduced the convective velocity field and the temperature structure of the solar photosphere using neutral iron line λ ≈ 639.3 nm profiles from the observations with high spatial resolution taken around the centre of the solar disc in the non-perturbed region. We obtained power spectra of vertical velocity and temperature variations at different photospheric levels in order to separate and study convective motions on different spatial scales. In the lower photosphere the main power is localized on the granular scales with a peak at scales of about 1-1.5 Mm (for the velocity variations) and 1.5 2 Mm (for the temperature variations) and it decreases with height. In the higher layers of the solar photosphere the peaks of the spectra of long-lived structures (T > 20 min) are slightly shifted to the larger scales (≈ 3 Mm at the height h = 400 km), but still present granulation. So, a separate regime of mesogranulaton at scales 5-10 Mm distinct from granulation by a power gap has not been found. Mesostructures appear as a part of a broad distribution of granular scales without further distinction from granulation.